2021
DOI: 10.1021/acs.analchem.0c04076
|View full text |Cite
|
Sign up to set email alerts
|

Flowing Atmospheric Pressure Afterglow for Ambient Ionization: Reaction Pathways Revealed by Modeling

Abstract: We describe the plasma chemistry in a helium flowing atmospheric pressure afterglow (FAPA) used for analytical spectrometry, by means of a quasi-one-dimensional (1D) plasma chemical kinetics model. We study the effect of typical impurities present in the feed gas, as well as the afterglow in ambient humid air. The model provides the species density profiles in the discharge and afterglow regions and the chemical pathways. We demonstrate that H, N, and O atoms are formed in the discharge region, while the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(155 reference statements)
1
7
0
Order By: Relevance
“…This is supported by recent modelling from the Bogaerts laboratory, which also identified reactive N O and O 3 neutral species in the afterglow [99]. The production of protonated water clusters by nitrogen dimer ions is favourable due to the high dipole moment and low ionization potential of water despite the water's low molar concentration in air.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…This is supported by recent modelling from the Bogaerts laboratory, which also identified reactive N O and O 3 neutral species in the afterglow [99]. The production of protonated water clusters by nitrogen dimer ions is favourable due to the high dipole moment and low ionization potential of water despite the water's low molar concentration in air.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…The model used herein accounted for 58 species and 739 reactions that revolved around the He, H and O products produced in a typical He/H 2 O plasma. The relevant reactions were taken from a previous study by Aghaei and Bogaerts [58], however no N containing reactions were included since high purity He (99.999%) was used throughout, and the capillary outlet is submerged and isolated from air. Rate equations, if not constant, are calculated using electron/gas temperature dependent reaction rates from literature and are integrated in time using the built-in solver.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, because of the various favorable associative ionization and conversion rates, [25][26][27] He 2 + has a greater population density than that of He + in He-based plasmas operated at pressures >5 torr. 28,29 Modeling studies on a DBD at atmospheric pressure 30 and a helium-flowing atmospheric pressure afterglow 31 showed that the He 2 + population is at least one order of magnitude larger than that of He + . One decay pathway for the He 2 + ion is through direct ion-electron dissociative recombination, yielding He* as a product.…”
Section: Two-dimensional Images Of Steady-state Ltp Emissionmentioning
confidence: 99%